CHINESE UNIVERSITY MEDIA CULTURE IN THE CONTEXT OF COVID-19 REVIEW, ISSUES AND DEVELOPMENT TRENDS - Zeng Chunlong (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Campus media culture is an active phenomenon in universities and an important part of the composition of campus culture. Especially with the rise of "We media", campus media culture leads the school trend and fashion, and has a significant influence on the thoughts and behaviors of teachers and students. After the outbreak of COVID-19, due to the frequent use of online classes, mobile phones or other electronic technologies for work or epidemic prevention, campus media has been more widely used, which has a greater impact on university teachers and students.This paper focuses on the special field of Chinese university media culture, expounds the concept and connotation of Chinese university campus media culture, combining the domestic and foreign scholars on this problem, Chinese university campus media culture itself problems and exist in the changes of the epidemic environment, looking forward to other future development trends.